Information science identity: Students' perspective. Issue 1 (22nd October 2020) - Ma, Yuanye; Goray, Cami
Abstract: We present a qualitative study that maps Library and Information Science (LIS) students' understanding of their information science identity. The mapping is achieved through exploring multiple aspects of this identity, including students' conceptualization of the field and related disciplines, their evaluation of coursework, and their future career expectations. Twelve semi‐structured interviews were conducted with undergraduate and graduate LIS students in the spring of 2020. Five themes were identified through the coding process, which include: how students conceptualized the field in general, the people focus in information science, students' explicit expression of difficulty in describing the field, coursework representative of information science, and how students relate information science studies to their intended career path. Leveraging the students' perspective to frame this identity question is valuable, because it offers an opportunity to understand the Library and Information Science identity in its formative stages.